Kinship Across the Black Atlantic Writing Diasporic Relations (Volume 23) - Adair, Gigi (Liverpool University Press, 2019)
'Kinship Across the Black Atlantic provides an outstanding analysis of new models and modes of family-making proposed by a range of key contemporary diasporic writers. Drawing upon a wealth of critical discussions of kinship drawn from anthropology, philosophy, feminism, queer studies, and more besides, Gigi Adair pursues a series of dazzling, detailed readings of the literary re-imagining of family-making across the black Atlantic. Ever alert to the pitfalls as well as the possibilities of fictionalising kinship anew, her vibrant analysis valuably uncovers the progressive modes of kinship that diasporic writing daringly and urgently proposes, often by reaching beyond the colonial-crafted constraints of heteronormativity, genealogy and biocentric myths of 'blood'.'